Structural stability for a thermal convection model with temperature-dependent solubility. (April 2015) - Ciarletta, M.; Straughan, B.; Tibullo, V.
Abstract: We study a problem involving thermosolutal convection in a fluid when the solute concentration is subject to a chemical reaction in which the solubility of the dissolved component is a function of temperature. When the spatial domain is a bounded one in R 2 we show that the solution depends continuously on the reaction rate using true a priori bounds for the solution when the chemical equilibrium function is an arbitrary function of temperature.